2019
DOI: 10.2169/internalmedicine.1403-18
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Pericarditis in which Oral Corticosteroid Therapy Was Effective

Abstract: IgG4-related diseases (IgG4-RDs) have recently been reported in many organs other than the salivary, pancreatic and hepatobiliary systems. A 64-year-old woman was referred to our department for her abdominal fullness and cardiomegaly on chest X-ray. After draining the pericardial fluid, her symptom promptly diminished, and pericardial friction rubbing became clearly audible. Elevated serum levels of IgG and IgG4 and ureteral wall thickening on computed tomography suggested IgG4-RD. After the initiation of oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The characteristic lymphoplasmacytic infiltration of IgG4-RD rarely involves the pericardium. In the active phase of pericardial inflammation, symptoms of acute pericarditis with/without pericardial effusion may predominate 23 . As the pericardial inflammation progresses to the chronic phase, symptoms related to pericardial constriction emerge, including polyserositis and pedal edema.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic lymphoplasmacytic infiltration of IgG4-RD rarely involves the pericardium. In the active phase of pericardial inflammation, symptoms of acute pericarditis with/without pericardial effusion may predominate 23 . As the pericardial inflammation progresses to the chronic phase, symptoms related to pericardial constriction emerge, including polyserositis and pedal edema.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of multidetector-row computed tomography (CT) and other imaging techniques has revealed that IgG4-RD lesions extend to cardiovascular organs, causing coronary periarteritis (CP), aortic periarteritis (AP), and pericardial thickening. 4 , 5 , 6 , 7 , 8 , 9 However, the factors that determine the affected sites are unknown. AP can lead to aortic aneurysm formation, which requires surgical or endovascular intervention.…”
mentioning
confidence: 99%